Where do I start? : researching your family in Australia and New Zealand - Hicks, Shauna (St Agnes, SA : Unlock the Past, 2018)
"Where do I start? is perhaps one of the most frequently asked questions from people interested in learning more about their family history. I wrote this research guide to present together in one place methodology and resources mentioned in my presentations to societies and libraries. Using various internet resources you can usually build a family pedigree quickly going back several generations. Then you spend more time filling in the details and getting to know your ancestors lives and the communities in which they lived. It is definitely not all online and this guide highlights some of the archives and libraries that you will become familiar with as you research your family history. It is more than a beginner's guide as it introduces researchers to a wide variety of resources and research methodology. There are many ways to research and record your family history. Even those who have been researching for some time will find new ideas and renewed motivation to seek out even more information on their ancestors. Family history is a learning process and you acquire new skills and knowledge as you progress. This book will help to guide you along the way"--Back cover.
Text and illustrations on end papers.
Includes bibliographical references (pages 89-90) and index.
Keywords: Genealogy -- Sources -- Handbooks, manuals, etc; Genealogy; Australia -- Genealogy; Australia -- Genealogy -- Handbooks, manuals, etc; New Zealand -- Genealogy; New Zealand -- Genealogy -- Handbooks, manuals, etc; Australian